2020
DOI: 10.1007/s10334-020-00833-9
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-free high-resolution 3D magnetization transfer imaging for simultaneous myocardial scar and cardiac vein visualization

Abstract: Objective To develop a three-dimensional (3D) high-resolution free-breathing magnetization transfer ratio (MTR) sequence for contrast-free assessment of myocardial infarct and coronary vein anatomy. Materials and methods Two datasets with and without off-resonance magnetization transfer preparation were sequentially acquired to compute MTR. 2D image navigators enabled beat-to-beat translational and bin-to-bin non-rigid motion correction. Two different imaging sequences were explored. MTR scar localization was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In summary, a reference protocol was implemented comprising 25 images with 25 distinct MT weightings (at fivedifferent frequency offsets log‐spaced between 1 and 7.7 kHz and five different MT FAs linearly spaced between 360 and 800°) partly based on previous work by the authors 26 . Next, MT parameter maps were calculated based on dictionary matching using all the acquired MT images and (independently acquired) T1 and T2 maps.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, a reference protocol was implemented comprising 25 images with 25 distinct MT weightings (at fivedifferent frequency offsets log‐spaced between 1 and 7.7 kHz and five different MT FAs linearly spaced between 360 and 800°) partly based on previous work by the authors 26 . Next, MT parameter maps were calculated based on dictionary matching using all the acquired MT images and (independently acquired) T1 and T2 maps.…”
Section: Methodsmentioning
confidence: 99%
“…In summary, a reference protocol was implemented comprising 25 images with 25 distinct MT weightings (at fivedifferent frequency offsets log-spaced between 1 and 7.7 kHz and five different MT FAs linearly spaced between 360 and 800°) partly based on previous work by the authors. 26 Next, MT parameter maps were calculated based on dictionary matching using all the acquired MT images and (independently acquired) T1 and T2 maps. Then, PSR and T B 2 values were calculated for all possible combinations of five MT weightings and the best combination was chosen based on maximizing the accuracy of the parameter values and the coefficient of determination of the match.…”
Section: Optimization and Validation In Phantomsmentioning
confidence: 99%
“…However, it has been suggested that certain confounders to MOLLI T 1 measurements may enhance clinical sensitivity. 137 As illustrated in Figure 7, this somewhat counter-intuitive phenomenon arises because some confounders (e.g., magnetization transfer 84,137,138 ) are sensitive to pathological alterations, leading to inflated effect size in certain disease entities compared to unbiased measurements. However, as a result of these confounders, the measurand in MOLLI is highly dependent on the sequence parameters (e.g., TR, flip angle, slice profile), the scanner specifications and tissue properties that are not related to the tissue T 1 time.…”
Section: Cardiac Tmentioning
confidence: 99%